2019
DOI: 10.1111/jcpp.13026
|View full text |Cite
|
Sign up to set email alerts
|

Atypical resting state neuromagnetic connectivity and spectral power in very preterm children

Abstract: Background Children born very preterm often display selective cognitive difficulties at school age even in the absence of major brain injury. Alterations in neurophysiological activity underpinning such difficulties, as well as their relation to specific aspects of adverse neonatal experience, remain poorly understood. In the present study, we examined interregional connectivity and spectral power in very preterm children at school age, and their relationship with clinical neonatal variables and long‐term outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
2
19
1
Order By: Relevance
“…In support of the view that neurophysiological connectivity may be associated with developmental outcomes in very preterm children, we recently found that extremely preterm (≤28 weeks gestation) and very preterm children (28–32 weeks gestation) had pronounced alterations in connectivity which were associated with both adverse neonatal experience and poorer behavioral and cognitive performance at school age (Kozhemiako et al, ). These findings, combined with the long‐established evidence of males being more affected by preterm birth that leads to poorer long‐term outcome, led us to hypothesize that preterm males are characterized by more pronounced inter‐regional connectivity alterations than preterm females.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In support of the view that neurophysiological connectivity may be associated with developmental outcomes in very preterm children, we recently found that extremely preterm (≤28 weeks gestation) and very preterm children (28–32 weeks gestation) had pronounced alterations in connectivity which were associated with both adverse neonatal experience and poorer behavioral and cognitive performance at school age (Kozhemiako et al, ). These findings, combined with the long‐established evidence of males being more affected by preterm birth that leads to poorer long‐term outcome, led us to hypothesize that preterm males are characterized by more pronounced inter‐regional connectivity alterations than preterm females.…”
Section: Introductionmentioning
confidence: 68%
“…A head model was created for each subject using a single shell method as implemented in FieldTrip toolbox (Oostenveld, Fries, Maris, & Schoffelen, ). For those participants who did not have a T1 MRI image recorded, the pool of 73 child MRIs was searched for the best‐matched MRI for participant, as implemented in our previous study (Kozhemiako et al, ). Specifically, to choose the best match we calculated the mean distance between each Polhemus point and the closest point on the skull surface, which was derived from segmented MRI image using Fieldtrip toolbox.…”
Section: Methodsmentioning
confidence: 99%
“…Procedural pain was also observed to be related to abnormal maturation of brain volumes at school age, including the hippocampus, amygdala, thalamus, striatum, globus pallidus, and cerebellum (125,126), and lower cortical thickness (127). Studies using magnetoencephalagraphy (MEG) found that differences in spontaneous gamma-to alpha-band oscillations in preterm-born school-age children were predicted by the number of invasive neonatal procedures, which, as suggested by the authors, might be attributed to alterations in thalamorcortical connectivity (128,129). Hence, the abnormal maturation observed in the neonatal period seems to persist into childhood, affecting brain regions implicated in the regulatory capacity to future stressors (see Table 1 for an overview).…”
Section: Neonatal Stress and Brain Developmentmentioning
confidence: 95%
“…Grunau and colleagues have highlighted the important adverse role of frequent painful and stressful invasive procedures (~10 per day) at a time of rapid brain development and programming of the hypothalamic‐pituitary‐adrenal (HPA) or stress axis (Grunau et al., 2006; Vinall & Grunau, 2014). Above and beyond clinical factors related to prematurity, these necessary invasive procedures are associated with physiological and behavioral indicators of hypo‐reactivity in the NICU (Grunau et al., 2005), physiological hyper‐reactivity to novelty in infancy (Grunau et al., 2004), and problems in behavioral development across childhood (Chau et al., 2019; Kozhemiako et al., 2019; Ranger et al., 2014) including greater internalizing behaviors (Ranger et al., 2014). To capture the stress of invasive procedures we use the term “pain‐related stress” (Grunau et al., 2006).…”
Section: Introductionmentioning
confidence: 99%